A Study on Soft S-Metric Spaces - Gunduz Aras, Cigdem; Bayramov, Sadi; Cafarli, Vefa (Communications in Mathematics and Applications, 2018)
The first aim of this paper is to define soft S-metric space and examine some of its properties. Later we define the concepts of soft continuous mapping, soft sequential continuous and investigate the relationship between them.
Keywords: Soft set; soft S-metric; soft sequential continuous mapping